2020
DOI: 10.1021/acsami.0c17540
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned 2D MoS2 Layers with Strain-Engineered Serpentine Patterns for High-Performance Stretchable Gas Sensors: Experimental and Theoretical Demonstration

Abstract: Two-dimensional (2D) molybdenum disulfide (MoS2) with vertically aligned (VA) layers exhibits significantly enriched surface-exposed edge sites with an abundance of dangling bonds owing to its intrinsic crystallographic anisotropy. Such structural variation renders the material with exceptionally high chemical reactivity and chemisorption ability, making it particularly attractive for high-performance electrochemical sensing. This superior property can be further promoted as far as it is integrated on mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 69 publications
3
26
0
Order By: Relevance
“…Figure 1b-g present the characterization data of these materials which were grown by a chemical vapor deposition (CVD)-based thermal sulfurization or tellurization of Pt thin films, similar to the growth of other 2D TMDs. [13,16,[18][19][20][21][22][23][24][25][26] Specific details regarding the growth conditions are found in the Experimental Section. Figure 1b displays a low-magnification cross-sectional transmission electron microscopy (TEM) image of a non-layered PtS thin film (left) as well as its corresponding high resolution TEM (HR-TEM) image (right).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1b-g present the characterization data of these materials which were grown by a chemical vapor deposition (CVD)-based thermal sulfurization or tellurization of Pt thin films, similar to the growth of other 2D TMDs. [13,16,[18][19][20][21][22][23][24][25][26] Specific details regarding the growth conditions are found in the Experimental Section. Figure 1b displays a low-magnification cross-sectional transmission electron microscopy (TEM) image of a non-layered PtS thin film (left) as well as its corresponding high resolution TEM (HR-TEM) image (right).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, vertically-aligned (VA) 2D MoS 2 layers have also been demonstrated as identified via HR-TEM (Fig. 6(d)), 57 showing uniformly-spaced vdW gaps. Moreover, integral VA 2D PtSe 2 layers have been observed via HR-TEM (Fig.…”
Section: Visualization Of Structural Disorders In 2d Tmd Layersmentioning
confidence: 93%
“…[50][51][52][53] Extensive efforts have been devoted to the direct visualization of the gaps. 57 Reproduced with permission from ref. 57 Copyright 2020 American Chemical Society.…”
Section: Van Der Waals Gapsmentioning
confidence: 99%
“…Several researchers have identified that semiconductor MoS 2 active sites are mostly located on the edge of the crystal structures, while the abundant basal plane is relatively less reactive for chemical reactions. , Therefore, it is necessary to modify the basal plane of MoS 2 to improve its reactivity. Among other methods, the doping process is one of the most promising techniques to modify the basal plane structure of MoS 2 because it modifies not only the structure but also the electronic and optical properties of MoS 2 . , The doping process by the substitution of the element could make different chemical bondings in the crystal lattice (expand or shrink), which could act as active site centers for the adsorption because of a strain in the crystal structure. , The strain in the crystal structure of MoS 2 increases the molecular adsorption ability including higher adsorption energy, closer adsorption distance, and better charge transfer ability …”
Section: Introductionmentioning
confidence: 99%